O tęsknotach poety: Myśli przez Ivana Hribovška podpowiedziane - Pszczoła, Joanna (Slavia Centralis, 2020)
On the poet’s longing. Thoughts whispered by Ivan Hribovšek In this article the author deals with the poetry of the Slovenian war poet, Ivan Hribovšek, and his story. In his homeland (under communist rule) he was rejected and condemned to oblivion. He and his poetry were ignored because he decided to join the guerrillas during the war and was later accused of treason. What is most interesting about his poetry is that it is not political at all; rather, this poetry is a lyrical reflection on God, love, death and the Earth, the eternal motifs of literature.